ANTREPRENORIATUL, SUPORT AL DEZVOLTĂRII UMANE: STUDIU DE CAZ PRIVIND ACTIVITĂȚILE ADMINISTRATIVE ȘI DE SUPORT ȘI ACTIVITĂȚILE PROFESIONALE, ȘTIINȚIFICE ȘI TEHNICE DIN REGIUNEA DE NORD-EST A ROMÂNIEI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Entrepreneurship, Support of Human Development. Case Study on Administrative and Support Activity and Professional, Scientific and Technical Activities in the North-East Region of RomaniaHuman development encompasses all aspects of human existence. Human development evolves through dimensions that define it, such as: enhancing human skills and creating appropriate conditions for people. Empowerment is quantified by long and healthy life, knowledge, decent standard of living, and creating appropriate conditions which involves participation in political and community life, environmental sustainability, gender and security, and human rights. As seen human development is sustainable only in the presence of these dimensions that support human dignity and develop through entrepreneurship. (UNDP, 2015)Entrepreneurship is one of the key factors of human development, implicitly of human dignity. In the first part, the paper proposes some important coordinates regarding human development in correlation with human dignity and entrepreneurship, respectively: entrepreneurship leads to the expansion of the set of human capacities and develops an objectiveoriented behavior, entrepreneurship is effective if there is coherent support of human capital that it it also creates if a good clustering of activities can be nsured, entrepreneurial performance is essential in human development, and the knowledge appropriately applied in business is the engine of human development through entrepreneurship. In the second part, the paper develops some important coordinates regarding the applicability of entrepreneurship in the North-East region of Romania. The case study refers to the development of business in the administrative and support activities and professional, scientific and technical activities. The decisions are mainly applicable in the mountain area.